1973
DOI: 10.1288/00005537-197309000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cochlea and kidney

Abstract: The not uncommon association in clinical practice of problems existing simultaneously in the kidney and ear, prompted a closer look at these two distant organs, revealing in fact that they may be comparable in a variety of ways. Anatomical similarities were seen especially at the ultra‐structural level. Physiological mechanisms of fluid and electrolyte balance are present in both organs, and this common function is reflected in similar pharmacological actions of certain drugs. Congenital syndromes which have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
3

Year Published

1975
1975
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(51 citation statements)
references
References 16 publications
0
47
1
3
Order By: Relevance
“…Alport (1927) described a case in which hearing loss was associated with a familial renal disease. Quick et al (1973) described the resemblance in the histological and biochemical pattern between the Cochlea and the Kidney, particularly that of the stria Vascularis and the glomerulus--both of which are epithelial structures and intimately associated with the Vascular system hence factors leading to changes in the Kidney which can bring about similar changes in the Cochlea also. Yassin et al (1966) examined 105 patients with renal failure and showed variable ENT manifestations, mainly in the form of epistaxis (17 cases), vertigo (50 cases), sore throat (7 cases), salivary adenitis (1 case), respiratory insufficiency (9 cases), and perceptive deafness ( 8 cases).…”
Section: Introductionmentioning
confidence: 99%
“…Alport (1927) described a case in which hearing loss was associated with a familial renal disease. Quick et al (1973) described the resemblance in the histological and biochemical pattern between the Cochlea and the Kidney, particularly that of the stria Vascularis and the glomerulus--both of which are epithelial structures and intimately associated with the Vascular system hence factors leading to changes in the Kidney which can bring about similar changes in the Cochlea also. Yassin et al (1966) examined 105 patients with renal failure and showed variable ENT manifestations, mainly in the form of epistaxis (17 cases), vertigo (50 cases), sore throat (7 cases), salivary adenitis (1 case), respiratory insufficiency (9 cases), and perceptive deafness ( 8 cases).…”
Section: Introductionmentioning
confidence: 99%
“…Abi struktūros atlieka aktyvią vandens ir elektrolitų pernašą, pasitelkdamos Na-K ATP-azę. Fermentas karboanhidrazė taip pat yra randamas tiek nefrone, tiek kraujagysliniame ruoželyje [2].…”
Section: įVadasunclassified
“…Sensorineural hearing impairment (SHI) has been reported in chronic renal failure (CRF) patients with a prevalence of 20-40% [1]. The aetiopathogenetic mechanisms reported included osmotic alteration resulting in loss of hair cells, collapse of the endolymphatic space, oedema and atrophy of specialized auditory cells and in some, complications of haemodialysis have been hypothesized [2][3][4].…”
Section: Introductionmentioning
confidence: 99%